Tinjauan Yuridis Pemberian Wilayah Izin Usaha Pertambangan Khusus Kepada Badan Usaha Milik Organisasi Kemasyaraktan Keagamaan Tanpa Mekanisme Lelang - Ilham, Fajar Hidayansyah; Anggraeni, Marchellina Shagyna (Jurnal Hukum & Pembangunan, 2024)
Natural resources is one of the essential aspects of life and human existence. Indonesia is known as a country with abundant natural resources. Therefore, their management must be conducted transparently to prevent corruption and ensure that natural resources are managed in the most efficient and beneficial way fore the community. If natural resources controlled by the state are not managed based on principles reflecting justice, there is a potential that the benefits will only be enjoyed by a small group of people. The mechanism of granting Special Mining Business Permits (WIUPK) through auction is one way to embody the principles of transparency, prevent corruption, and ensure that natural resources are managed in the most efficient and fair manner. However, recently, president jokowi’s government issued Government Regulation No. 25 of 2024, amending Government Regulation No. 96 of 2021 on the implementation of Mineral and Coal Mining Business Activities, which grants special treatment to business entities owned by religious community organizations to obtain WIUPK trough a priority offer mechanism without an auction process. This study uses a normative juridicial method with a legislative approach. The results of the study show that there is a conflict of norms in granting WIUPK to business entities owned by religious community organizations without an auction mechanism, as well as several issues arising from the enforcement of these norms.